The Common: “Immediate-Universal”? - Huchet, Stéphane (Farol, 2025)
By “common,” we usually refer to a type of art distancing artists and the public from the erudite frameworks that have characterized art throughout its history. Revisiting here some brief points from an essay published by the author of this article in 2023 and outlining a reflection on the paradoxes of the concept, I defend the thesis of a “common” whose ideal, sociologically grounded in the idea of ​​proximity to everyday life, also conveys a universalizing vision. The very old concept of sensus communis in Kant allows us to support this thesis, since every “common,” within the aesthetic logic of experience, almost explicitly creates an integrative relationship with the idea of ​​community. Whether micro or macro, the “common” needs to be thought of beyond sociology to affirm its full belonging to the aesthetic game as a potentially unifying mechanism of sensibilities. A supposedly novel category recycles old motivations.